Pengaruh Matakuliah Kewirausahaan Terhadap Minat Berwirausaha Pada Mahasiswa Pendidikan Vokasional Desain Fashion Universitas Ngudi Waluyo - Rina Purwanti; Jaya Ramadey Bangsa (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The aim of this research is to determine the influence of entrepreneurship courses on students' interest in becoming entrepreneurs in the Fashion Design Vocational Education study program. This research is important because research on the influence of entrepreneurship courses on students' interest in entrepreneurship in the Fashion Design Vocational Education study program is the first to be conducted. Entrepreneurship courses are one of the courses that students must take. The respondents selected and used in this research were students of the Fashion Design Vocational Education study program. This research was conducted using a survey method using a list of questions (questionnaire) as the main instrument in collecting primary data. From the results of the research and discussion, it can be concluded that entrepreneurship courses have an influence on interest in entrepreneurship among students in the Fashion Design Vocational Education study program at Ngudi Waluyo University, because by taking entrepreneurship courses students gain insight into the concept of entrepreneurship and train entrepreneurial skills which include entrepreneurial characteristics, motivation, business plan, human resources, production and marketing which can increase interest in entrepreneurship and gain experience which can change students' mindset and behavior so that they have an interest in entrepreneurship